2018
DOI: 10.1099/jgv.0.001130
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of accessory genes 3a, 3b, 5a or 5b from avian coronavirus infectious bronchitis virus induces an attenuated phenotype both in vitro and in vivo

Abstract: Avian coronavirus infectious bronchitis virus (IBV) infects domestic fowl, resulting in respiratory disease and causing serious losses in unprotected birds. Its control is mainly achieved by using live attenuated vaccines. Here we explored the possibilities for rationally attenuating IBV to improve our knowledge regarding the function of IBV accessory proteins and for the development of next-generation vaccines with the recently established reverse genetic system for IBV H52 based on targeted RNA recombination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…The viral load of the respiratorytype strain, rH120 in the different tissues indicated that the viral levels in the trachea, early following infection were significantly higher than those of rIBYZ, which indicates that the ability of the virus to attached to trachea epithelial cells of the rH120 strain was stronger than that of the rIBYZ strain. However, during the later time points post-infection, the level of the rH120 strain was significantly lower than rIBYZ, which suggests that the virulence of IBV depends both on tissue invasion and viral replication ability, as well as other functions mediated by other viral proteins (e.g., non-structural, structural, and accessory proteins) [6,29,[58][59][60]. The reduction of the viral load at 5 dpi in the group infected with the rIBYZ strain may be associated with the necrosis and shedding of the trachea epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…The viral load of the respiratorytype strain, rH120 in the different tissues indicated that the viral levels in the trachea, early following infection were significantly higher than those of rIBYZ, which indicates that the ability of the virus to attached to trachea epithelial cells of the rH120 strain was stronger than that of the rIBYZ strain. However, during the later time points post-infection, the level of the rH120 strain was significantly lower than rIBYZ, which suggests that the virulence of IBV depends both on tissue invasion and viral replication ability, as well as other functions mediated by other viral proteins (e.g., non-structural, structural, and accessory proteins) [6,29,[58][59][60]. The reduction of the viral load at 5 dpi in the group infected with the rIBYZ strain may be associated with the necrosis and shedding of the trachea epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…recombinant viruses. By using reverse genetics, a previous report showed that the replicase gene of IBV is a determinant of pathogenicity (Armesto et al, 2009) and recent studies have shown that IBV pathogenicity is also due to the accessory proteins (Laconi et al, 2018;van Beurden et al, 2018). In order to establish the mechanisms, further study by reverse genetics and animal studies is needed to verify the association between changes in the genome sequence and the pathogenicity of IBV strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of S1 sequence analysis might not be solely sufficient to explain the changes observed in IBV antigenicity, tissue tropism, and pathogenicity. In recent years, several studies have noted that viral replication, pathogenicity, and immune escape might be modulated by non-structural and accessory viral proteins in IBV and other coronaviruses (Armesto et al, 2009;Chen et al, 2009;Laconi et al, 2018;Zheng et al, 2008;van Beurden et al, 2018). These findings emphasize the importance of studying the characteristics of the complete genomes of coronaviruses and their associations with antigenicity, tissue tropism, and pathogenicity.…”
Section: Introductionmentioning
confidence: 97%
“…IBV also possesses two accessory genes, Gene 3 and Gene 5, which have been shown to be dispensable for virus replication in cell culture Youn et al, 2005;Hodgson et al, 2006;Bentley et al, 2013). However, it seems that the deletion of accessory genes 3a, 3b, 5a or 5b from IBV could induce an attenuated phenotype both in vitro and in vivo (Laconi et al, 2018;van Beurden et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, infectious fulllength clones of coronaviruses have only been established at the beginning of the 21 st century (Casais et al, 2001). Subsequently, reverse genetics was successfully applied to study the role of accessory genes in viral replication Youn et al, 2005;Laconi et al, 2018), the potential of IBV as a vaccine vector (Britton et al, 2012;Bentley et al, 2013), the virulence determinants of the Beaudette and M41 strains (Fang et al, 2007;Maria et al, 2009;Keep et al, 2018), and the relationship between the S gene and tissue tropism of the virus (Casais et al, 2003;Britton et al, 2005;Promkuntod et al, 2013;Shan et al, 2018). However, to the best of our knowledge, all existing reverse genetics systems for IBV were either based on Vero cell-adapted Beaudette strain, which is non-pathogenic in chickens (Geilhausen et al, 1973), or the Mass-type strains, which are genetic quite distant from the prevalent QX-type strains.…”
Section: Introductionmentioning
confidence: 99%